Effect of Sex Form and Sowing Dates on Seed Germination of Indian Valerian (Valeriana jatamansi Jones) under Temperate Himalayan Conditions - Tayu, Achili; Ayoob, Bilkees; Gangoo, S. A.; Sofi, P. A.; Singh, Ameerjeet; Malik, A. R. (Indian Forester, 2024)
The present experiment was conducted at SKUAST-K to study the florai and morphological variation In different sex forms of Valeriana jatamansi Jones and to Investigate the effect of sex form and sowing dates on germination parameters of Indian valerian. Two different sex forms, viz., gynoecious and bisexual, were identified during the flowering phase in March from two-year old seedlings of Valeriana Jatamansi. The floral variation, viz., gynodloecism, larger hermophrodite flowers in comparison to gynoecious flowers, colour or size morphotypes in female flowered plants were observed. Except for plant height, there was no significant difference in the morphological parameters studied, viz., leaf length, leaf width, leaf area, number of flowering stalk, petiole length and petiole diameter. Gynoecious plants (49.27 cm) were found to be taller than that of bisexual plants (38.76 cm). Sex forms, viz., gynoecious and bisexual have no significant effect on germination of Indian valerian, whereas the germination parameters were found significantly affected by different sowing dates (June, July, August and September). The highest germination percentage (60.13%), germination value (4.49), germination energy (38.63%) and germination speed (3.50) were obtained, when the seeds were sown In the month of June. Our research revealed that the seeds o f Indian valerian should be sown Immediately after collection, as the delay in seed sowing might result in loss of seed viability.